Sustainable urban features and their relation with environmental satisfaction in commercial public space: an example of the Great Bazaar of Tabriz, Iran. Issue 1 (2nd January 2019) - Ouria, Mahmoud
ABSTRACT: This paper investigates sustainable urban aspects of the Great Bazaar of Tabriz (GBT) in Iran, classified as the world's largest covered bazaar. Qualitative and statistical research methods employed to analyze the sustainable features of the (GBT) and compare them against four dimensions of the sustainable development model. The results of the public satisfaction survey employed, calculated using SPSS for the GBT, show that the majority of approximately 78% of the interviewees are satisfied with the bazaar's environment, whereas a minority of approximately 16% declared that they are less happier with the environment. Accordingly, the 'friendly atmosphere' has the highest impact on satisfaction with approximately 92%, and the 'role of trade unions', with approximately 54%, is the lowest factor impacting public satisfaction with the bazaar's spatial configurations. Historical and vernacular architectural elements are the main strength of the GBT; the lack of infrastructures to expand e-commerce activities is seen as a weakness; the potential grow number of costumer shopping at the GBT is identified as an opportunity, and international sanctions are interpreted as a threat. Finally, recommendations regarding a more comprehensive approach toward the sustainability of the GBT and the flourishing tourism activity in the Tabriz, in general, are presented.